Seasonal patterns and prevalence of respiratory pathogens in children with acute respiratory infections in Wuhan, China - Zegang Wu; Chenglin Ye; Guolei Wang; Jun’e Ma; Li Yuan; Xuan Xiao; Chengliang Zhu (Journal of Infection in Developing Countries, 2025)
Introduction: Acute respiratory infection (ARI) is the major cause of disease and death in children. This study aimed to analyze the prevalence of common pathogens causing ARI in children aged 6 years or younger in Wuhan and the impact of the Coronavirus Disease 2019 (COVID-19) pandemic on the detection rate of these pathogens.